Long‐Range Hydrophilic Attraction between Water and Polyelectrolyte Surfaces in Oil. Issue 48 (27th October 2016) - Shi, Chen; Yan, Bin; Xie, Lei; Zhang, Ling; Wang, Jingyi; Takahara, Atsushi; Zeng, Hongbo
Abstract: The outstanding water wettability and the capability of polyelectrolyte surfaces to spontaneously clean oil fouling are determined by their wetting mechanism in the surrounding medium. Here, we have quantified the nanomechanics between three types of polyelectrolyte surfaces (i.e. zwitterionic, cationic, and anionic) and water or oil drops using an atomic force microscope (AFM) drop probe technique, and elucidated the intrinsic wetting mechanisms of the polyelectrolyte surfaces in oil and water media. The measured forces between oil drops and polyelectrolyte surfaces in water can be described by the Derjaguin‐Landau‐Verwey‐Overbeek (DLVO) theory. Surprisingly, strong long‐range attraction was discovered between polyelectrolyte surfaces and water drops in oil, and the strongest interaction was measured for the polyzwitterion. This unexpected long‐range "hydrophilic" attraction in oil could be attributed to a strong dipolar interaction because of the large dipole moment of the polyelectrolytes. Our results provide new nanomechanical insights into the development of novel polyelectrolyte‐based materials and coatings for a wide range of engineering, bioengineering, and environmental applications. Abstract : Wetting phenomena : A long‐range hydrophilic attraction in an oil medium was discovered between water and zwitterionic, cationic, and anionic polyelectrolyte molecules using an atomic force microscopy technique. The unexpected strong attraction could possibly be attributed to a strong dipolar interaction due to the large dipole moment of the polyelectrolyte molecules.